Maquripe [sic] Bay, Trinidad, B.W.I. - (:unkn) unknown (Waterman, the Hatter, Clothier and Outfitter, [Trinidad and Tobago]; Printed in England, 2011)
A view of Maqueripe Bay located on the northern coastline of Chaguaramas, Trinidad.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bays--Trinidad and Tobago; Inlets--Trinidad and Tobago; Beaches--Trinidad and Tobago; Bathing beaches--Trinidad and Tobago; Maqueripe Bay